2017
DOI: 10.1155/2017/4237973
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin B Prevents Hind Limb from Ischemia-Reperfusion-Induced Oxidative Stress and Inflammation via MAPK/NF-κB Pathways in Rats

Abstract: Schisandrin B (ScB), isolated from Schisandra chinensis (S. chinensis), is a traditional Chinese medicine with proven cardioprotective and neuroprotective effects. However, it is unclear whether ScB also has beneficial effects on rat hind limb ischemia/reperfusion (I/R) injury model. In this study, ScB (20 mg/kg, 40 mg/kg, and 80 mg/kg) was administered via oral gavage once daily for 5 days before the surgery. After 6 h ischemia and 24 h reperfusion of left hind limb, ScB reduced I/R induced histological chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Evodiamine inhibited IκBα phosphorylation to inactivate NF-κB expression to relieve zymosan-induced inflammation ( Fan et al., 2017 ). Schisandrin B or psoralen ameliorated chondrocyte inflammation and osteoarthritis, oxidative stress injury, and DSS-induced colitis via suppression of the NF-κB/MAPK signaling pathways, followed by decreased inflammatory cytokines ( Liu et al., 2015a , b ; Li et al., 2017 ; Zhu et al., 2017 ; Ran et al., 2018 ). We have previously found that SSW inhibited P38 MAPK mRNA expression to downregulate colonic epithelial cell apoptosis in colonic mucosa in mice with colitis ( Zhao et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evodiamine inhibited IκBα phosphorylation to inactivate NF-κB expression to relieve zymosan-induced inflammation ( Fan et al., 2017 ). Schisandrin B or psoralen ameliorated chondrocyte inflammation and osteoarthritis, oxidative stress injury, and DSS-induced colitis via suppression of the NF-κB/MAPK signaling pathways, followed by decreased inflammatory cytokines ( Liu et al., 2015a , b ; Li et al., 2017 ; Zhu et al., 2017 ; Ran et al., 2018 ). We have previously found that SSW inhibited P38 MAPK mRNA expression to downregulate colonic epithelial cell apoptosis in colonic mucosa in mice with colitis ( Zhao et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…And it belongs to dibenzocyclooctadiene derivatives chemically. In general, Schisandrin B has shown various benefits in different organs and diseases, such as osteoarthritis, renal fibrosis, and myocardial ischemia ( Ran et al, 2018 ; Zhao et al, 2018 ; Cao et al, 2019 ), and it has been reported to regulate several signaling pathways, including NF-κB, MAPK, PI3K/AKT, and Nrf2/HO-1 pathways ( Zhu et al, 2017 ; Feng et al, 2018 ; Zhao et al, 2018 ; You et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that MAPKs (p38, ERK, and JNK) signaling pathways are highly associated with oxidative stress-induced cell death ( 41 - 43 ). Other studies have shown that overexpression of IDO-1 protein inhibited the activation of Akt and MAPKs signaling pathways and regulated apoptotic protein expression levels in neuronal cells under excessive oxidative stress ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%